Strategi Keunggulan Kompetitif Home Industri Sewel Khas Socah Ditinjau dari Perspektif Etika Bisnis Islam - Faizah Fairani; Luluk Hanifah (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2023)
This study aims to determine the competitive advantage strategy of Socah's typical home industry from the perspective of Islamic business ethics. Qualitative method with descriptive approach. This is done by observing directly or going down to the field by conducting interviews and observations of the home industry entrepreneurs in Socah Village, Bangkalan Regency. The results of the study show that of the 7 home industry producers, 2 home industries (28.6%) apply a cost leadership strategy. Meanwhile, 3 home industries (42.8%) implemented a differentiation strategy. Of the remainder (28.6%), they focus more on a differentiation focus strategy. While Islamic business ethics from 7 producers, 2 home industries (28.6%) apply the principle of unity (monotheism), the principle of justice or balance there are 4 producers (57.2%) and 7 or (100%) producers apply the principle of free will, responsibility and compassion.